Exploration of Genetic Variants Associated with Lung Cancer: A Comprehensive Review (Bangladesh Pharmaceutical Journal, 2025)
Lung cancer (LC) is a widespread and prevalent disease with a high death rate. The occurrence of this terrible disease is greatly influenced by genetic, occupational and environmental risk factors. Therefore, the present review aimed to investigate and accumulate the information regarding the causative gene of lung cancer. The articles included in this study were retrieved from various online sources, including Cochrane Library, Google Scholar, EMBASE, PubMed and Web of Science databases up to October 2024. Data were extracted based on the PRISMA 2020 guidelines. The study recognized several genetic mutations that are accountable for the progression of lung cancer. The most common identified lung cancer associated with genes include XRCC1, XRCC4, KRAS, TP53, EGFR, PI3KCA, ERCC2/XPD MET, ALK1, BRAF, HER2, LTKB-1/STK11, AKT1 and MAP2K1. Additionally, HER2, MAP2K1/MEK1, AKT, NRAS and various combinations of co-occurring mutations were also noted as stimulators of this cancer. These genes instigate lung cancer either by impairing DNA repair efficiency or interacting with various signaling pathways that result in cell proliferation, differentiation, angiogenesis, invasion and metastasis, such as, PI3k/AKT (phosphatidylinositol 3-kinase/protein kinase B) pathway, MAPKs (mitogen-activated protein) pathway, PKC (protein kinase C), JAK/STAT (Janus kinase/signal transducer and activator of transcription) pathway, as well as RAS signaling. Studying epigenetic mechanisms in lung cancer is crucial to understand the genetic variant linked to the disease and identify potential therapeutic targets and molecular targets of drugs.Bangladesh Pharmaceutical Journal 28(1): 114-125, 2025 (January)